The intermediate effects of third-party payment platform in China. (11th October 2019) - Huang, Weilun; Dai, Xiaozhen
The purpose of this paper is to discuss the consumer behaviour of third-party payment (TPP) in China, and the intermediate effects for the quality variables of TPP platform, which are its platform conveniences, applications conveniences, and social networks, from consumers' perceived values and risks of TPP to the consumer TPP behaviour. Furthermore, this paper tries to analyse the moderated effects of people's gender, age and monthly income on their TPP behaviour and the above intermediate effects. According to the results of a questionnaire survey in China and their statistical analysis, respondents' TPP behaviour variables are their average TPP frequency is three times a day, and their average TPP amount is RMB 1, 664 a month. It is found that the intermediate effects for the quality variables of TPP platform are significant. What is more, it is proven that the gender, age, and monthly income of people would moderate their TPP behaviour and the intermediate effects for the application conveniences and social networks of TPP platform.